Pendugaan Nilai Heterosis dan Daya Gabung Beberapa Komponen Hasil pada Persilangan Dialel Penuh Enam Genotipe Cabai (Capsicum annuum L.) - Sriani Sujiprihati; Rahmi Yunianti; Muhamad Syukur; U Undang (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
The objective of this study was to  estimate the  heterosis and heterobeltiosis of thirty chili hybrids, the general combining ability (GCA), and the specific combining ability (SCA) of six chili (Capsicum annuum L.)   inbred lines. The experiment was conducted from October 2005 to March 2006 at IPB Experiment Field, Cikabayan, Darmaga. Randomized Complete Blocked Design was used with three replications.  All characters were significantly different for heterosis, heterobeltiosis, general and specific combining ability. Significant  differences were noted in reciprocal effect for fruit weight, and yield per plant. Hybrid IPB C-2 x IPC C-3 and IPB C-3 x IPB C-1 had positive heterosis and heterobeltiosis values for all variables observed. IPB C-2 showed the highest GCA for yield per plant and fruit length, IPB C-3 and IPB C-7 showed high GCA for yield per plant, fruit length, fruit width, and fruit weight. Crosses having high SCA for all variables observed were IPB C-1 x IPB C-3 and IPB C-2 x IPB C-3. Cross combination of IPB C-2 x IPB C-3 was the best hybrid.   Key words: chili, heterosis, heterobeltiosis, combining ability, full diallel